Karakter CEO, Family Board Members, dan Internasionalisasi Perusahaan Keluarga yang Terdaftar di BEI - Rahmat Setiawan; Aditya Sahrul; Nabilah Ratnaduhita Firjatullah (Jurnal Ekonomi Efektif, 2023)
The purpose of this research is to examine the influence of the CEO Characteristics and family board members on a family firms internationalization listed on the Indonesia Stock Exchange. This research is using multiple linear regression model, the data is acquired from report finance company published from period 2011-2016. Dependent variables used is internationalization proxied with foreign sales to total sales. Independent variables in this research are education level of the CEO, Gender of the CEO, family board member of commissioner and family board member of director. The results of this research shows that the education level of the CEO has a positif effect on internationalization, the CEO's gender is not significant to internationalization, while the family board member of commissioners and family board member of director are negatifly afflicted against internationalization.